Master batch for flexible freight bag as well as preparation method and application of master batch

By optimizing the components and ratio of the mother -in -law, combined with Mao metallic low -density low -density polyethylene, polyester fiber and other materials, the lack of container bags in terms of mechanical strength and toughness. Performance and longer service life.

CN119371736APending Publication Date: 2025-01-28HEBEI WANHEFENG PACKAGE CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411573686.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

Existing container bags have shortcomings in terms of mechanical strength and toughness, which are prone to wire breakage and difficult to process, which affects production efficiency and causes waste of resources.

Method used

By controlling the components and ratio of the mother -in -law, the linear low -density polyethylene, polyester fiber, silane -modified carbon nanotuba, methyl acrylic hydroglceride elastic bodies, ammonium polyacryamate, and ammonium composite are used. The combination of sex cloud mother, ternary cluster and decentralizers enhances the strength, toughness, conductivity and anti -pollution of the container material.

Benefits of technology

It significantly improves the comprehensive performance of the container bag, enhances its mechanical strength and toughness, improves the electrical conductivity and pollution resistance, extends the service life and reduces the waste of resources.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of macromolecular flexible freight bags, and particularly discloses a master batch for a flexible freight bag as well as a preparation method and application thereof. In the master batch for the flexible freight bag, the mLLDPE has good melt strength and tensile strength, and the polyester fiber has excellent strength, elastic recovery, wear resistance and hair sticking resistance, is presented in a fiber form, and has certain strength after being compounded with other raw materials; the carbon nano tube has a conductive effect, and silane is adopted to modify the carbon nano tube, so that the hydrophobicity, dispersity and antifouling property of the carbon nano tube can be improved, and the compatibility of the carbon nano tube with other materials is improved; the glycidyl methacrylate grafted elastomer can improve the toughness of the container bag and improve the compatibility of the ammonium polyacrylate modified mica and the resin matrix; the ammonium polyacrylate is adopted to modify the mica, so that the suspension stability and homogeneity of the mica can be improved, and the mechanical strength of the container bag is further improved; and the terpolymer can improve the compatibility among the raw materials, so that the comprehensive performance of the container bag is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer container bags, and in particular to a masterbatch for container bags, a preparation method and application thereof. Background Art

[0002] Container bags, also known as ton bags or ton bags, are a kind of flexible transport packaging container. They are moisture-proof, dust-proof, radiation-resistant, firm and safe, and have sufficient structural strength. In order to prevent the accumulation of excessive static electricity during transportation and cause explosion, container bags also have antistatic effects. They are widely used in the transportation and packaging of bulk, powdery, granular and blocky items such as food, grains, medicines, chemicals, and minerals, which greatly improves the efficiency of loading, unloading and handling. Container bags are generally made of polypropylene, polyethylene and other textiles. However, the existing container bags still need to be improved in terms of mechanical strength and toughness. They are easy to break during use and difficult to process, which not only greatly affects production, but also causes waste of resources. Summary of the invention

[0003] In view of the above problems, the present invention provides a masterbatch for container bags, a preparation method and application thereof, and by controlling the components and proportions of the masterbatch for container bags, the strength, toughness, conductivity and anti-fouling properties of the container bag material are significantly improved.

[0004] In order to solve the above technical problems, the technical solution provided by the present invention is: In a first aspect, the present invention provides a masterbatch for container bags, comprising the following raw material components in parts by weight: 30 to 45 parts of metallocene linear low-density polyethylene, 20 to 30 parts of polyester fiber, 20 to 28 parts of silane-modified carbon nanotubes, 5 to 10 parts of glycidyl methacrylate grafted elastomer, 1 to 2 parts of ammonium polyacrylate modified mica, 5 to 8 parts of terpolymer and 1 to 3 parts of dispersant.

[0005] Compared with the prior art, the masterbatch for container bags provided by the present invention uses metallocene linear low-density polyethylene (mLLDPE) and polyester fiber as resin matrices. The metallocene linear low-density polyethylene has good melt strength and tensile strength, and the polyester fiber has excellent strength, elastic recovery ability, abrasion resistance and non-stick characteristics, so that the woven container bags are strong and durable, and can quickly restore to their original state, and have a certain anti-fouling ability. At the same time, the polyester fiber is in the form of fibers and has a certain strength after being compounded with other raw materials; carbon nanotubes have a conductive effect, which can prevent the container bags from accumulating static electricity during use, but directly adding carbon nanotubes can easily cause a decrease in the mechanical properties of the resin matrix. The present invention uses silane to modify the carbon nanotubes, which can improve the hydrophobicity of the carbon nanotubes and the dispersibility of the carbon nanotubes, so that the silane-modified carbon nanotubes are not easy to agglomerate, and their compatibility with other materials is improved. At the same time, the prepared container bags have It has good antifouling property; glycidyl methacrylate grafted elastomer can not only improve the toughness of container bags, but also significantly improve the compatibility between ammonium polyacrylate modified mica and resin matrix, so that ammonium polyacrylate modified mica can be better dispersed in the resin matrix to play its role; mica is a rigid particle, which can significantly improve the mechanical strength of container bags, but its compatibility with the resin matrix is ​​extremely poor. Direct addition will not only fail to improve its mechanical strength, but will cause stratification due to poor dispersibility, thereby reducing the overall performance of the container bags. The present invention uses ammonium polyacrylate to modify mica, which can improve the suspension stability of mica, improve the fusion of the surface of the powder material with other components, and then improve the homogeneity of mica dispersion. Long-term storage will not cause stratification and sedimentation, thereby improving the mechanical properties of the container bags; the terpolymer is used as a surface modifier, which can significantly improve the compatibility between the raw materials, thereby improving the comprehensive performance of the container bags.

[0006] The present invention improves the compatibility between the raw material components by limiting the raw materials and their proportions of the masterbatch for the container bag, so that the raw material components have a synergistic effect, and greatly improves the comprehensive performance of the container bag.

[0007] Preferably, the density of the metallocene linear low-density polyethylene is 0.90 g / cm 3 ~0.92g / cm 3 , comonomer content ≥20%.

[0008] Exemplary, metallocene linear low density polyethylene is available from The Dow Chemical.

[0009] Preferably, the density of the polyester fiber is 1.35 g / cm 3 ~1.40g / cm 3 , the breaking strength is 3cN / dtex~5cN / dtex.

[0010] For example, the polyester fiber was purchased from Taian Songze Composite Materials Co., Ltd.

[0011] Preferably, the method for preparing silane-modified carbon nanotubes comprises the following steps: The trimethoxysilane is dissolved in an alcohol solution, and carbon nanotubes are added thereto for reflux reaction to obtain silane-modified carbon nanotubes.

[0012] More preferably, the trimethoxysilane is C10~C20 alkyltrimethoxysilane.

[0013] For example, the trimethoxysilane is selected from at least one of dodecyltrimethoxysilane, hexadecyltrimethoxysilane, and octadecyltrimethoxysilane.

[0014] Further preferably, the alcohol solution is an ethanol aqueous solution with a volume concentration of 90% to 95%.

[0015] More preferably, the mass volume ratio of the trimethoxysilane, the alcohol solution and the carbon nanotubes is (3-5) g: (180-220) mL: 100 g.

[0016] Further preferably, the reflux reaction time is 2h~3h.

[0017] For example, after the reflux reaction is completed, the following steps may be performed: solid-liquid separation, washing, drying, and crushing to obtain silane-modified carbon nanotubes.

[0018] Preferably, the glycidyl methacrylate grafted elastomer is selected from at least one of glycidyl methacrylate grafted styrene-butadiene-styrene copolymer and glycidyl methacrylate grafted linear low-density polyethylene.

[0019] Preferably, the preparation method of the ammonium polyacrylate modified mica comprises the following steps: The ammonium polyacrylate aqueous solution is fluidized and sprayed on the surface of mica, and then dried to obtain the ammonium polyacrylate modified mica.

[0020] Further preferably, the particle size of the mica is D50=3μm~10μm.

[0021] Further preferably, the mass ratio of the ammonium polyacrylate aqueous solution to the mica is (5-10):100.

[0022] Further preferably, the mass concentration of the ammonium polyacrylate aqueous solution is 10% to 15%.

[0023] Preferably, the terpolymer is an ethylene-acrylate-maleic anhydride terpolymer.

[0024] For example, ethylene-acrylate-maleic anhydride terpolymer (EMH) was purchased from Arkema, France.

[0025] The preferred terpolymer of the present invention is a polar polymer material. As a surface modifier, the polar carboxyl end group can produce a strong interaction with the hydroxyl end group rich in the mica surface, and the non-polar flexible chain can be entangled with the resin matrix, thereby improving the surface properties between the two phases and enhancing the interfacial bonding.

[0026] Preferably, the dispersant is selected from at least one of polyethylene wax and polypropylene wax.

[0027] In the present invention, the dispersant can further improve the compatibility of the raw material components.

[0028] In a second aspect, the present invention provides a method for preparing the masterbatch for container bags, comprising the following steps: S1, weighing various raw material components according to the designed ratio, mixing the ammonium polyacrylate modified mica and the glycidyl methacrylate grafted elastomer, plasticizing, and thinning to obtain fine particles; S2, mixing the fine particles with metallocene linear low-density polyethylene, polyester fiber, silane-modified carbon nanotubes, terpolymer and dispersant, melt-extruding and granulating to obtain masterbatch for container bags.

[0029] The method for preparing masterbatch for container bags provided by the present invention comprises the following steps: firstly plasticizing ammonium polyacrylate modified mica and glycidyl methacrylate grafted elastomer, the two can form a soft-encased hard core-shell structure, thereby further improving the compatibility of the ammonium polyacrylate modified mica with a resin matrix, and the glycidyl methacrylate grafted elastomer can also improve the subsequent compatibility with polypropylene; then, the masterbatch for container bags with excellent performance is obtained by mixing with other raw material components for granulation, which is beneficial to improving the comprehensive performance of subsequent container bags.

[0030] Preferably, in S1, the temperature of the plasticizing is 120° C. to 140° C., and the plasticizing time is 10 min to 15 min.

[0031] Preferably, in S2, the melt extrusion adopts a twin-screw extruder, and the twin-screw extrusion temperature is set from the feed section to the die as follows: 175℃~190℃, 180℃~195℃, 185℃~195℃, 190℃~200℃, 190℃~200℃, 190℃~200℃, 195℃~200℃, 190℃~200℃, 180℃~190℃ and 170℃~180℃, and the main engine speed is 90rpm~110rpm.

[0032] In a third aspect, the present invention provides a fiber material for container bags, comprising the following raw material components in percentage by weight: 50% to 65% of the masterbatch for container bags and 35% to 50% of polypropylene.

[0033] The fiber material for container bags provided by the present invention adopts polypropylene as a resin matrix. Polypropylene has the characteristics of low density, good heat resistance, good mechanical properties, stable chemical properties, good electrical insulation performance, and easy processing and molding, but also has the disadvantages of low impact strength, easy softening and deformation at high temperature, easy aging, high low temperature brittleness, insufficient toughness, and large processing and molding shrinkage. The present invention compounds polypropylene with mLLDPE and polyester fiber in a masterbatch for container bags, and can exert the synergistic effect of the three. At the same time, the glycidyl methacrylate grafted elastomer and the terpolymer in the masterbatch for container bags can react with polypropylene, enhance the interface bonding force between the three resin matrices, and then improve the compatibility between the three resin matrices, so as to improve the comprehensive performance of the container bags.

[0034] Preferably, the density of the polypropylene is 0.89 g / cm 3 ~0.90g / cm 3 .

[0035] For example, polypropylene was purchased from Sinopec Maoming Branch.

[0036] In a fourth aspect, the present invention provides a method for preparing the fiber material for bulk bags, comprising the following steps: The masterbatch for bulk bags and polypropylene are melt-spun to obtain fiber materials for bulk bags.

[0037] Preferably, the melt spinning adopts a melt spinning machine, and the temperature settings from the feed inlet to the spinneret hole are: 205℃~210℃, 240℃~245℃, 255℃~260℃, 255℃~260℃, 245℃~250℃ and 235℃~240℃, the spinning rate is 450m / s~480m / s, and the drafting multiple is 7 times~7.5 times. DETAILED DESCRIPTION

[0038] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0039] In the present invention, unless otherwise specified, all materials are commercially available products.

[0040] Example 1 This embodiment provides a masterbatch for container bags and a preparation method thereof.

[0041] The masterbatch for container bags is composed of the following raw material components in parts by mass: 40 parts of mLLDPE, 23 parts of polyester fiber, 23 parts of silane-modified carbon nanotubes, 8 parts of glycidyl methacrylate grafted styrene-butadiene-styrene copolymer, 1.5 parts of ammonium polyacrylate modified mica, 6 parts of EMH and 2 parts of polyethylene wax.

[0042] The preparation method of masterbatch for container bags comprises the following steps: S1, preparation of silane-modified carbon nanotubes: 4 g of dodecyltrimethoxysilane was dissolved in 200 mL of 95% (v / v) ethanol aqueous solution, 100 g of carbon nanotubes was added and refluxed for 2.5 h, then the solid-liquid was separated, and the solid was washed, dried and crushed in sequence to obtain silane-modified carbon nanotubes.

[0043] S2, preparation of ammonium polyacrylate modified mica: A 12 wt % ammonium polyacrylate aqueous solution was fluidized and sprayed on the surface of mica with a D50 of 8 μm, the mass ratio of the ammonium polyacrylate aqueous solution to the mica being 8:100, and the solution was dried to obtain ammonium polyacrylate modified mica.

[0044] It should be noted that there is no order of precedence between S1 and S2.

[0045] S3, weighing various raw material components according to the designed ratio, mixing the ammonium polyacrylate modified mica with the glycidyl methacrylate grafted styrene-butadiene-styrene copolymer, plasticizing at 130°C for 12 minutes, thinning out sheets, and shearing to obtain fine particles.

[0046] S4, the fine granules are mixed with mLLDPE, polyester fiber, silane-modified carbon nanotubes, EMH and polyethylene wax, and a twin-screw extruder is used for melt extrusion and granulation. The twin-screw extrusion temperatures from the feed section to the die are set as follows: 180°C, 185°C, 190°C, 195°C, 195°C, 195°C, 198°C, 195°C, 185°C and 175°C, and the main engine speed is 100rpm to obtain masterbatch for container bags.

[0047] Example 2 This embodiment provides a masterbatch for container bags and a preparation method thereof.

[0048] The masterbatch for container bags is composed of the following raw material components in parts by mass: 35 parts of mLLDPE, 28 parts of polyester fiber, 26 parts of silane-modified carbon nanotubes, 7 parts of glycidyl methacrylate grafted linear low-density polyethylene, 1.8 parts of ammonium polyacrylate modified mica, 7 parts of EMH and 1.5 parts of polypropylene wax.

[0049] The preparation method of masterbatch for container bags comprises the following steps: S1, preparation of silane-modified carbon nanotubes: 3.5 g of hexadecyltrimethoxysilane was dissolved in 190 mL of 92% (v / v) ethanol aqueous solution, 100 g of carbon nanotubes was added and refluxed for 2.5 h, then the solid-liquid separation was performed, and the solid was washed, dried and crushed in sequence to obtain silane-modified carbon nanotubes.

[0050] S2, preparation of ammonium polyacrylate modified mica: A 13 wt % ammonium polyacrylate aqueous solution was fluidized and sprayed on the surface of mica with a D50 of 5 μm, the mass ratio of the ammonium polyacrylate aqueous solution to the mica being 7:100, and then dried to obtain ammonium polyacrylate modified mica.

[0051] It should be noted that there is no order of precedence between S1 and S2.

[0052] S3, weighing various raw material components according to the designed ratio, mixing ammonium polyacrylate modified mica with glycidyl methacrylate grafted linear low-density polyethylene, plasticizing at 125°C for 12 minutes, thinning out sheets, and shearing to obtain fine particles.

[0053] S4, the fine granules are mixed with mLLDPE, polyester fiber, silane-modified carbon nanotubes, EMH and polypropylene wax, and a twin-screw extruder is used for melt extrusion and granulation. The twin-screw extrusion temperatures from the feed section to the die are set as follows: 185°C, 190°C, 190°C, 195°C, 195°C, 195°C, 197°C, 195°C, 185°C and 175°C, and the main engine speed is 100rpm to obtain masterbatch for container bags.

[0054] Example 3 This embodiment provides a masterbatch for container bags and a preparation method thereof.

[0055] The masterbatch for container bags is composed of the following raw material components in parts by mass: 30 parts of mLLDPE, 30 parts of polyester fiber, 20 parts of silane-modified carbon nanotubes, 10 parts of glycidyl methacrylate grafted styrene-butadiene-styrene copolymer, 1 part of ammonium polyacrylate modified mica, 8 parts of EMH and 1 part of polyethylene wax.

[0056] The preparation method of masterbatch for container bags comprises the following steps: S1, preparation of silane-modified carbon nanotubes: 3 g of octadecyltrimethoxysilane was dissolved in 180 mL of 95% (v / v) ethanol aqueous solution, 100 g of carbon nanotubes was added and refluxed for 2 h, then the solid-liquid was separated, and the solid was washed, dried and crushed in sequence to obtain silane-modified carbon nanotubes.

[0057] S2, preparation of ammonium polyacrylate modified mica: A 10 wt % ammonium polyacrylate aqueous solution was fluidized and sprayed on the surface of mica with a D50 of 10 μm, the mass ratio of the ammonium polyacrylate aqueous solution to the mica being 10:100, and the solution was dried to obtain ammonium polyacrylate modified mica.

[0058] It should be noted that there is no order of precedence between S1 and S2.

[0059] S3, weighing various raw material components according to the designed ratio, mixing the ammonium polyacrylate modified mica with the glycidyl methacrylate grafted styrene-butadiene-styrene copolymer, plasticizing at 120°C for 15 minutes, thinning out sheets, and shearing to obtain fine particles.

[0060] S4, the fine particles are mixed with mLLDPE, polyester fiber, silane-modified carbon nanotubes, EMH and polyethylene wax, and melt-extruded and granulated by a twin-screw extruder. The twin-screw extrusion temperatures from the feed section to the die are set as follows: 175°C, 180°C, 185°C, 190°C, 190°C, 190°C, 195°C, 190°C, 180°C and 170°C, and the main engine speed is 110rpm to obtain masterbatch for container bags.

[0061] Example 4 This embodiment provides a masterbatch for container bags and a preparation method thereof.

[0062] The masterbatch for container bags is composed of the following raw material components in parts by mass: 45 parts of mLLDPE, 20 parts of polyester fiber, 28 parts of silane-modified carbon nanotubes, 5 parts of glycidyl methacrylate grafted linear low-density polyethylene, 2 parts of ammonium polyacrylate modified mica, 5 parts of EMH and 3 parts of polypropylene wax.

[0063] The preparation method of masterbatch for container bags comprises the following steps: S1, preparation of silane-modified carbon nanotubes: 5 g of dodecyltrimethoxysilane was dissolved in 220 mL of 90% (v / v) ethanol aqueous solution, 100 g of carbon nanotubes was added and refluxed for 3 h, then the solid-liquid was separated, and the solid was washed, dried and crushed in sequence to obtain silane-modified carbon nanotubes.

[0064] S2, preparation of ammonium polyacrylate modified mica: A 15 wt % ammonium polyacrylate aqueous solution was fluidized and sprayed on the surface of mica with a D50 of 3 μm, the mass ratio of the ammonium polyacrylate aqueous solution to the mica being 5:100, and then dried to obtain ammonium polyacrylate modified mica.

[0065] It should be noted that there is no order of precedence between S1 and S2.

[0066] S3, weighing various raw material components according to the designed ratio, mixing ammonium polyacrylate modified mica with glycidyl methacrylate grafted linear low-density polyethylene, plasticizing at 140°C for 10 minutes, thinning out sheets, and shearing to obtain fine particles.

[0067] S4, the fine particles are mixed with mLLDPE, polyester fiber, silane-modified carbon nanotubes, EMH and polypropylene wax, and melt-extruded and granulated by a twin-screw extruder. The twin-screw extrusion temperatures from the feed section to the die are set as follows: 190°C, 195°C, 195°C, 200°C, 200°C, 200°C, 200°C, 190°C and 180°C, and the main engine speed is 90rpm to obtain masterbatch for container bags.

[0068] Comparative Example 1 This comparative example provides a masterbatch for container bags and a preparation method thereof.

[0069] The raw material components of the masterbatch for container bags are similar to those in Example 1, except that the polyester fiber is replaced with mLLDPE of the same mass. The other conditions are the same as those in Example 1 and will not be described in detail.

[0070] The preparation method of the masterbatch for container bags is similar to that of Example 1, except that in S4, the polyester fiber is replaced with mLLDPE of the same mass. The remaining conditions are the same as those of Example 1 and will not be described in detail.

[0071] Comparative Example 2 This comparative example provides a masterbatch for container bags and a preparation method thereof.

[0072] The raw material components of the masterbatch for container bags are similar to those in Example 1, except that mLLDPE is replaced with polyester fiber of the same mass. The remaining conditions are the same as those in Example 1 and will not be described in detail.

[0073] The method for preparing the masterbatch for container bags is similar to that in Example 1, except that in S4, mLLDPE is replaced with polyester fiber of the same quality. The remaining conditions are the same as those in Example 1 and will not be described in detail.

[0074] Comparative Example 3 This comparative example provides a masterbatch for container bags and a preparation method thereof.

[0075] The raw material components of the masterbatch for container bags are similar to those in Example 1, except that the silane-modified carbon nanotubes are replaced with carbon nanotubes of the same mass. The remaining conditions are the same as those in Example 1 and will not be described in detail.

[0076] The method for preparing the masterbatch for container bags is similar to that of Example 1, except that step S1 is omitted and the silane-modified carbon nanotubes in S4 are replaced with carbon nanotubes of the same mass. The remaining conditions are the same as those of Example 1 and will not be described in detail.

[0077] Comparative Example 4 This comparative example provides a masterbatch for container bags and a preparation method thereof.

[0078] The raw material components of the masterbatch for container bags are similar to those in Example 1, except that the glycidyl methacrylate grafted styrene-butadiene-styrene copolymer is replaced with styrene-butadiene-styrene copolymer of the same mass. The remaining conditions are the same as those in Example 1 and will not be described in detail.

[0079] The preparation method of the masterbatch for container bags is similar to that of Example 1, except that in S3, the glycidyl methacrylate grafted styrene-butadiene-styrene copolymer is replaced with styrene-butadiene-styrene copolymer of the same mass. The remaining conditions are the same as those of Example 1 and will not be described in detail.

[0080] Comparative Example 5 This comparative example provides a masterbatch for container bags and a preparation method thereof.

[0081] The raw material components of the masterbatch for container bags are similar to those in Example 2, except that the glycidyl methacrylate grafted styrene-butadiene-styrene copolymer is replaced with the same mass of maleic anhydride grafted styrene-butadiene-styrene copolymer. The remaining conditions are the same as those in Example 2 and will not be described in detail.

[0082] The preparation method of the masterbatch for container bags is similar to that of Example 2, except that in S3, the glycidyl methacrylate grafted styrene-butadiene-styrene copolymer is replaced with the same mass of maleic anhydride grafted styrene-butadiene-styrene copolymer. The remaining conditions are the same as those of Example 2 and will not be described in detail.

[0083] Comparative Example 6 This comparative example provides a masterbatch for container bags and a preparation method thereof.

[0084] The raw material components of the masterbatch for container bags are similar to those in Example 2, except that the ammonium polyacrylate-modified mica is replaced with mica of the same mass. The remaining conditions are the same as those in Example 2 and will not be described in detail.

[0085] The method for preparing the masterbatch for container bags is similar to that of Example 2, except that in S3, the ammonium polyacrylate-modified mica is replaced with mica of the same mass. The remaining conditions are the same as those of Example 2 and will not be described in detail.

[0086] Comparative Example 7 This comparative example provides a masterbatch for container bags and a preparation method thereof.

[0087] The raw material components of the masterbatch for container bags are similar to those in Example 2, except that EMH is replaced with polypropylene wax of the same quality. The remaining conditions are the same as those in Example 2 and will not be described in detail.

[0088] The preparation method of the masterbatch for container bags is similar to that of Example 2, except that in S4, EMH is replaced with polypropylene wax of the same quality. The remaining conditions are the same as those of Example 2 and will not be described in detail.

[0089] Application Example 1 This application example provides a fiber material for container bags, which is composed of the following raw material components in percentage by weight: 55% of the masterbatch for container bags in Example 1 and 45% of polypropylene.

[0090] The method for preparing fiber material for bulk bags comprises the following steps: The masterbatch for bulk bags and polypropylene are put into a melt spinning machine for melt spinning. The temperatures from the feed port to the spinneret hole are set to 208°C, 243°C, 258°C, 258°C, 248°C and 238°C, respectively. The spinning rate is 460m / s and the drafting multiple is 7 times to obtain fiber materials for bulk bags.

[0091] Application Example 2 This application example provides a fiber material for container bags, which is composed of the following raw material components in percentage by weight: 60% of the masterbatch for container bags in Example 2 and 40% of polypropylene.

[0092] The method for preparing fiber material for bulk bags comprises the following steps: The masterbatch for bulk bags and polypropylene are put into a melt spinning machine for melt spinning. The temperatures from the feed port to the spinneret hole are set to 207°C, 242°C, 257°C, 257°C, 247°C and 237°C, respectively. The spinning rate is 470m / s and the drafting multiple is 7 times to obtain fiber materials for bulk bags.

[0093] Application Example 3 This application example provides a fiber material for bulk bags, which is composed of the following raw material components in percentage by weight: 50% of the masterbatch for bulk bags of Example 3 and 50% of polypropylene.

[0094] The method for preparing fiber material for bulk bags comprises the following steps: The masterbatch for bulk bags and polypropylene are put into a melt spinning machine for melt spinning. The temperatures from the feed port to the spinneret hole are set to 205°C, 240°C, 255°C, 255°C, 245°C and 235°C, respectively. The spinning rate is 480m / s and the drafting multiple is 7 times to obtain fiber materials for bulk bags.

[0095] Application Example 4 This application example provides a fiber material for container bags, which is composed of the following raw material components in percentage by weight: 65% of the masterbatch for container bags of Example 4 and 35% of polypropylene.

[0096] The method for preparing fiber material for bulk bags comprises the following steps: The masterbatch for bulk bags and polypropylene are put into a melt spinning machine for melt spinning. The temperatures from the feed port to the spinneret hole are set to 210°C, 245°C, 260°C, 260°C, 250°C and 240°C, respectively. The spinning rate is 450m / s and the drafting multiple is 7 times to obtain fiber materials for bulk bags.

[0097] Comparative Application Examples 1~7 Comparative Application Examples 1 to 7 respectively provide a fiber material for a bulk bag, which is similar to the raw material components of Application Example 1, except that the masterbatch for the bulk bag in Example 1 is replaced by the masterbatch for the bulk bag in Comparative Examples 1 to 7 respectively.

[0098] The proportion and preparation method of the fiber material for the container bag are the same as those in Application Example 1 and will not be described in detail.

[0099] Comparative Application Example 8 This application example provides a fiber material for container bags, which is composed of the following raw material components in percentage by weight: 60% of the masterbatch for container bags in Example 2 and 35% to 50% of the condensation product of terephthalic acid and ethylene glycol.

[0100] The preparation method of the fiber material for container bags is similar to that of Application Example 2, except that polypropylene is replaced by a condensation product of phthalic acid and ethylene glycol.

[0101] Performance Testing The fiber materials for container bags provided in Examples 1 to 4 and Comparative Application Examples 1 to 8 were subjected to performance tests. According to GB / T14337-1993 standard, a YG021-50 single yarn strength tester was used to measure the breaking strength and breaking elongation of the fibers. Each sample was tested 3 times and the average value was taken. The test results are shown in Table 1.

[0102] The fiber materials for container bags provided in the corresponding examples 1 to 4 and comparative application examples 1 to 8 were woven into splines, and the mechanical properties of the splines were tested. The test results are shown in Table 1. Among them, the tensile splines were tested in accordance with the GB / T1040-92 standard, the specimen was dumbbell-shaped, and the tensile rate was 20mm / min. The bending performance was tested in accordance with the GB / T9341-2000 standard, the bending spline size was 80mm×10mm×4mm, the span was 64mm, and the pressure head rate was 20mm / min. The notched impact strength was tested in accordance with the GB / 1843-1996 standard, with a V-shaped notch, a specimen size of 80mm×10mm×4mm, and a notch depth of 1mm.

[0103] Table 1 Performance test results of fiber materials for container bags provided by application examples and comparative application examples

[0104] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modification, equivalent substitution or improvement made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A masterbatch for container bags, characterized in that: The invention comprises the following raw material components in parts by weight: 30 to 45 parts of metallocene linear low-density polyethylene, 20 to 30 parts of polyester fiber, 20 to 28 parts of silane-modified carbon nanotubes, 5 to 10 parts of glycidyl methacrylate grafted elastomer, 1 to 2 parts of ammonium polyacrylate modified mica, 5 to 8 parts of terpolymer and 1 to 3 parts of dispersant.

2. The masterbatch for container bags according to claim 1, characterized in that: The density of the metallocene linear low-density polyethylene is 0.90 g / cm 3 ~0.92g / cm 3 , comonomer content ≥ 20%; The density of the polyester fiber is 1.35 g / cm 3 ~1.40g / cm 3 , the breaking strength is 3cN / dtex~5cN / dtex.

3. The masterbatch for container bags according to claim 1, characterized in that: The glycidyl methacrylate grafted elastomer is selected from at least one of glycidyl methacrylate grafted styrene-butadiene-styrene copolymer or glycidyl methacrylate grafted linear low-density polyethylene; The terpolymer is an ethylene-acrylate-maleic anhydride terpolymer; The dispersant is selected from at least one of polyethylene wax and polypropylene wax.

4. The masterbatch for container bags according to claim 1, characterized in that: The preparation method of silane-modified carbon nanotubes comprises the following steps: dissolving trimethoxysilane in an alcohol solution, adding carbon nanotubes to carry out a reflux reaction, and obtaining silane-modified carbon nanotubes; The preparation method of ammonium polyacrylate modified mica comprises the following steps: fluidizing and spraying an ammonium polyacrylate aqueous solution on the surface of mica, and drying to obtain the ammonium polyacrylate modified mica.

5. The masterbatch for container bags according to claim 4, characterized in that: The trimethoxysilane is C10~C20 alkyltrimethoxysilane; The alcohol solution is an ethanol aqueous solution with a volume concentration of 90% to 95%; The mass volume ratio of the trimethoxysilane, the alcohol solution and the carbon nanotubes is (3-5) g: (180-220) mL: 100 g; The reflux reaction time is 2h~3h.

6. The masterbatch for container bags according to claim 4, characterized in that: The mass ratio of the ammonium polyacrylate aqueous solution to the mica is (5-10):100; The mass concentration of the ammonium polyacrylate aqueous solution is 10% to 15%.

7. The method for preparing a masterbatch for container bags according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1, weighing various raw material components according to the designed ratio, mixing the ammonium polyacrylate modified mica and the glycidyl methacrylate grafted elastomer, plasticizing, and thinning to obtain fine particles; S2, mixing the fine particles with metallocene linear low-density polyethylene, polyester fiber, silane-modified carbon nanotubes, terpolymer and dispersant, melt-extruding and granulating to obtain masterbatch for container bags.

8. The method for preparing masterbatch for container bags according to claim 7, characterized in that: In S1, the plasticizing temperature is 120°C to 140°C, and the plasticizing time is 10min to 15min; In S2, the melt extrusion adopts a twin-screw extruder, and the twin-screw extrusion temperature is set from the feed section to the head as follows: 175℃~190℃, 180℃~195℃, 185℃~195℃, 190℃~200℃, 190℃~200℃, 190℃~200℃, 195℃~200℃, 190℃~200℃, 180℃~190℃ and 170℃~180℃, and the main engine speed is 90rpm~110rpm.

9. A fiber material for container bags, characterized in that: The invention comprises the following raw material components in percentage by weight: 50% to 65% of the masterbatch for container bags as described in any one of claims 1 to 6 or the masterbatch for container bags prepared by the method for preparing the masterbatch for container bags as described in any one of claims 7 to 8 and 35% to 50% of polypropylene.

10. The method for preparing fiber material for container bags according to claim 9, characterized in that: The following steps are involved: The masterbatch for bulk bags and polypropylene are melt-spun to obtain fiber materials for bulk bags.